Effect of Religion on Domestic Violence Perpetration Among American Adults - Mitchell, Cassidy (2019)
After Hirschi and Stark’s Hellfire and Delinquency (1969), researchers have been seeking to determine whether there is a correlational link between religion and crime. This paper seeks to add to the literature by correlating domestic violence with four elements of religion (use of belief to solve everyday problems, prayer frequency, religious importance, and attendance of worship) that correspond with the four elements of Hirschi’s social control theory (attachment, commitment, belief, and involvement, respectively) (1969). It also includes male victims of domestic violence among female victims, unlike most previous literature. Using a series of logistic regression models, only attendance of worship, the variable that signified involvement, had statistical significance in any model, which may signify the need to focus more on the behavioral measures of social control theory rather than the attitudinal measures